Effect of patient-centered care implementation and quality of service on patient satisfaction - Wahyuni, Sri; Nurlaila, Nurlaila; Daulay, Aqwa Naser (LPMP Imperium, 2025)
This study aims to determine how implementing patient-centered care and service quality affects patient satisfaction at MM Hospital in Medan. This study utilizes a quantitative research methodology, employing multiple linear regression analysis. All statistical tests were conducted using SPSS version 25 software. The study's population includes patients at MM Hospital in Medan in 2024. Primary data was gathered through questionnaires distributed to 100 hospital patients. Additionally, secondary data was collected from journals, books, and previous research relevant to the topic. The findings indicate that implementing patient-centered care does not significantly affect patient satisfaction; however, implementing service quality has a significant impact on patient satisfaction. This research provides practical insights, helping hospitals assess patient satisfaction levels during each visit to MM Hospital. Public interest statements Recognizing the crucial role of service quality in patient satisfaction, the hospital should focus on enhancing service quality in all departments. This improvement can involve training staff in effective communication, responsiveness, and empathy, ensuring patients feel valued and cared for during their visits. Note: Early Version articles are published as standalone pieces and will later be compiled into issues prior to print publication. These Early Version articles will not appear in journal keyword searches, will not be included in article searches, and will not receive a DOI (Digital Object Identifier) until they are officially published in an issue.